Influence of Nanoparticles on the Dielectric Response of a Single Component Resin Based on Polyesterimide - Hardoň, Štefan; Kúdelčík, Jozef; Baran, Anton; Michal, Ondrej; Trnka, Pavel; Hornak, Jaroslav (Polymers, 2022)
The influence of various types of nanoparticle fillers with the same diameter of 20 nm were separately incorporated into a single component impregnating resin based on a polyesterimide (PEI) matrix and its subsequent changes in complex relative permittivity were studied. In this paper, nanoparticles of Al2O3 and ZnO were dispersed into PEI (with 0.5 and 1 wt.%) to prepare nanocomposite polymer. Dielectric frequency spectroscopy was used to measure the dependence of the real and imaginary parts of complex relative permittivity within the frequency range of 1 mHz to 1 MHz at a temperature range from +20 °C to +120 °C. The presence of weight concentration of nanoparticles in the PEI resin has an impact on the segmental dynamics of the polymer chain and changed the charge distribution in the given system. The changes detected in the 1H NMR spectra confirm that dispersed nanoparticles in PEI lead to the formation of loose structures, which results in higher polymer chain mobility. A shift of the local relaxation peaks, corresponding to the α-relaxation process, and higher mobility of the polymer chains in the spectra of imaginary permittivity of the investigated nanocomposites was observed.
Keywords: 1H NMR measurements; aluminium oxide; zinc oxide; polyesterimide; dielectric spectroscopy; dielectric relaxation